P256 Respiratory muscle strength measurements in primary school children. (15th November 2016) - Gharbawi, NTS; Gaillard, EA; Viskaduraki, M; Beardsmore, CS
Abstract : Background: Previous tests of respiratory muscle strength have rarely included measurements of inspiratory pressure. As part of a study looking at ethnic differences in respiratory muscle strength, we have measured maximum inspiratory and expiratory pressures in primary school children. Aim: We sought to determine the success rate and within-test repeatability of respiratory muscle strength measurements. Methods: We measured spirometry, height and weight and respiratory muscle strength by measuring maximal inspiratory and expiratory pressure (MIP and MEP) using Carefusion Vyntus in children aged 5–11 yr. Children breathed through a mouthpiece and pneumotachograph attached to a shutter, while wearing a noseclip. After a period of tidal breathing the child breathed in to total lung capacity and then tried to exhale forcibly against the shutter. We measured maximal (peak) expiratory pressure (MEP). For measurements of MIP, the child exhaled towards residual volume before making an inspiratory effort against the occlusion. Manoeuvres were excluded if the peak pressures were less than 3.50 kPa. We reported the largest pressures recorded, provided that the second-best was no more than 20% below the best. We calculated the percent difference between best and 2nd best manoeuvres and compared mean percentage differences in MIP and MEP. Results: Two hundred and thirty-one children were studied. We obtained MEP on 199 and MIP on 216, and paired data for MIP and MEP on 165 (87 boys and 78 girls). Overall, MIP was higher than MEP (mean (SD) MIP = 7.26 (1.92) kPa, MEP = 6.64 (1.76) kPa, p = 0.002). However, MEP tended to be bigger than MIP when the values were smaller (in the younger, smaller children) (Figure ). There was no significant difference between%difference MIP and%difference MEP (mean (SD) 5.50 ± 4.29 and 4.68 ± 3.96 kPa respectively, p = 0.07). Conclusion: The success rates of MIP and MEP measurements were 94% and 86% respectively, suggesting that MIP was easier for the children to perform. The success rate for paired measurements was 71%. The repeatability of inspiratory and expiratory pressures was not different. We speculate that the change with age between which measurement was greatest (MIP or MEP) may reflect dysanaptic muscle development.